2004
DOI: 10.2174/1568008043339767
|View full text |Cite
|
Sign up to set email alerts
|

The HIV-1 Tat Protein: A Multifaceted Target for Novel Therapeutic Opportunities

Abstract: Transcription of the integrated HIV-1 proviral genome is an essential step in the retrovirus life cycle and thus an appealing target for chemotherapeutic intervention to restrict retroviral replication. A fundamental role in this process is exerted by the viral protein Tat, a powerful transactivator of viral gene expression. This protein binds a structured RNA sequence at the 5'-ends of all nascent viral mRNAs and promotes transcription by mediating the recruitment to the viral promoter of cellular factors req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 0 publications
0
17
1
Order By: Relevance
“…Therefore the mechanism by which I-mfa and HIC inhibit transcription may involve recruitment of P-TEFb to the transcription complex rather than a direct effect on its kinase activity. Our studies with Tat truncations (Figure 5(d)) do not support the conclusion 10 that HIC binds to the Tat nuclear localization signal in its basic domain (aa [49][50][51][52][53][54][55][56][57]. Moreover, we did not observe relocalization of Tat to the cytoplasm in the presence of HIC.…”
Section: Effect Of the I-mfa Domains On P-tefb-dependent Transcriptioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Therefore the mechanism by which I-mfa and HIC inhibit transcription may involve recruitment of P-TEFb to the transcription complex rather than a direct effect on its kinase activity. Our studies with Tat truncations (Figure 5(d)) do not support the conclusion 10 that HIC binds to the Tat nuclear localization signal in its basic domain (aa [49][50][51][52][53][54][55][56][57]. Moreover, we did not observe relocalization of Tat to the cytoplasm in the presence of HIC.…”
Section: Effect Of the I-mfa Domains On P-tefb-dependent Transcriptioncontrasting
confidence: 76%
“…Tat's interaction with TAR RNA is mediated via its arginine/lysine-rich basic domain. In addition to its major role in recruiting P-TEFb, Tat interacts with numerous cellular proteins to facilitate HIV-1 infection (for reviews see [52][53][54][55]. We and others have previously shown that HIC interacts with first exon Tat (aa 1-72) in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Tat being originally discovered as the main transactivator of the viral genome, its inhibition has been initially approached by means of intracellular inhibitors (Giacca, 2004; Richter and Palù, 2006) aimed at the impairment of Tat nuclear translocation or of Tat/TAR interaction. More recently, when the biological relevance of extracellular Tat was assessed, a whole new set of extracellular inhibitors was developed (Rusnati and Presta, 2002b;.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, several drugs inhibiting different aspects of Tat transactivation are currently being tested. Different classes of compounds have been shown to specifically inhibit viral transcription by: (i) binding the TAR sequence, (ii) binding Tat, (iii) inhibiting PTEF-b components and (iv) generally inhibiting transactivation by mechanisms not yet well defined (Giacca, 2004). Small molecules that inhibit the splicing activity of SR proteins have also been shown to efficiently repress viral replication in peripheral blood mononuclear cells (PBMC) with little cell toxicity (Bakkour, et al, 2007).…”
Section: Future Prospectivementioning
confidence: 99%